Consumers’ Nostalgic Re-Engagement with Media in Emerging Markets: Emotional Needs, Content Overload, and Exposure - Yadav, Rohit; Hollebeek, Linda; Gaižutis, Algis; Yadav, Mohit (Organizations and Markets in Emerging Economies, 2025)
Grounded in uses-and-gratifications (U&G) theory, this research examines how millennials (Gen Y) nostalgically re-engage with media content and its outcomes in the emerging market context of India. The authors posit that nostalgia serves as both an emotional driver and a coping mechanism for digital overload, extending U&G theory by incorporating socially moderated gratifications beyond individual motives. Drawing on survey data (n=510) and using structural equation modeling to analyze the data, the authors find that while emotional needs and time of exposure boost nostalgic media engagement, perceived content overload reduces it. This engagement, in turn, enhances social sharing and emotional content attachment, with social connectedness moderating this effect. By showing that gratifications are not just individual (but also socially moderated) and by theorizing nostalgia as a coping mechanism against digital overload, the findings underscore that nostalgic re-engagement fulfils dual personal/social roles. Overall, the results detail the pathways and moderating factors influencing nostalgic media re-engagement, offering novel insight into the effect of individual motivations and social interactions on content consumption. Finally, the results reveal pertinent managerial implications, e.g., by suggesting the importance of reducing content overload (e.g., through curated recommendations), fostering social bonding via user-generated content, and incorporating nostalgic features like “memory lanes” and throwback content.
Keywords: nostalgia; consumer engagement; uses and gratification; Generation Y; Millenials; Emotional needs